Analisis contextual teaching and learning (CTL) pada buku teks pelajaran fisika SMA kelas X semester 2 - Putri Aulia; Desnita Desnita; Akmam Akmam; Silvi Yulia Sari (PILLAR OF PHYSICS EDUCATION, 2019)
The purpose of this study was found out the physics textbooks for senior high school Grade X Semester 2 has facilitated the implementation of contextual teaching and learning in senior high school. This research used descriptive method, where data collection used purposive sampling method. The population in this study are all senior high school physics textbooks grade X used in Indonesia and circulating in West Sumatra. The sample in this study were four physics texbooks Grade X Semester 2 in  senior high school used by several schools in West Sumatra. Colecting of data used instrument which contains seven component of contextual teaching and learning, which are translated into 39 items. The results showed that the presentation of physics textbooks for grade X semester 2 had facilitated the Implementation of the contextual teaching and learning. Textbook that greatly facilitate the implementation of a contextual teaching and learning and are suitable to use by schools is Sunardi’s book, which have an average value of 85% on the very facilitating category. While the textbook that has the lowest value is Marthen Kanginan's book with an average value of 63%  which is categorized as facilitating.